Talitridae (Amphipoda, Gammaridea) from the Brazilian coastline - Serejo, Cristiana S. (Zootaxa, 2004)
Surveys along the Brazilian coastline yielded material for the re-description of four semi-terrestrial talitrid species: the Brazilian endemics Chelorchestia darwinii (M ller, 1864), Pseudorchestoidea brasiliensis (Dana, 1853), which is transferred to Atlantorchestoidea gen. nov., and Talorchestia tucurauna (M ller, 1864); and the Atlantic Platorchestia monodi (Mateu et al., 1986). The syntype series of P. platensis (Kroyer, 1845) was examined and a lectotype and paralectotypes designated. A key for the talitrid species of the Brazilian coastline including some sibling species of Platorchestia monodi is provided.